Principals’ Optimism, Teachers’ Psychological Safety and Job Performance in Secondary Schools of Enugu State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
Leader optimism is a resource that have been shown to impact a leader’s capacity to positively influence followers towards successful job performance even in the face of crisis or insecurity. This study investigated the relationship between principals’ optimism, teachers’ psychological safety and job performance in Awgu Education Zone of Enugu State. Three null hypotheses were tested at 0.05 level of significance.  A correlational research design was employed using a sample of 250 teachers drawn through simple random sampling method. Principals’ optimism in insecurity, teachers’ psychological safety and job performance were measured using scales adapted from previous studies with reliability indices ranging from 0.71 to 0.83. The data analyzed using Pearson Product Moment Correlation revealed that there was a moderate negative relationship between principals’ optimism and teachers’ psychological safety and a positive relationship between teachers’ psychological safety and teachers’ job performance. The findings imply that the display of optimism by school principals in the context of the current state of insecurity in the country can dampen teachers’ sense of psychological safety thereby impede on the performance of their teaching responsibilities.  Based on the findings, it was recommended among other things that mechanisms to boost optimism among principals such as counselling by psychologists, organization of workshops for fostering principals’ optimism and creating awareness training campaign to be organized by the schools’ governing boards and Post-Primary Schools Management Board on school leaders’ optimism.